Ictiofauna como bioindicador de calidad del agua en el río carrizal - Chávez Loor, Jonathan Rafael (2019)
The research aimed to assess the quality of water in the Carrizal River based on the presence of ichthyofauna. The result was the establishment of six sampling stations (P01… P06) which are influenced by recreational, urban activities, liquid discharges from a local banana, among others. A total of 8 species of ichthyofauna were identified; being the most and least representative (Moenkhausia sp (bongo) and Hoplias microlepis (guanchiche), respectively). The Shannon Wiener index calculated for the stations ranged between 0.76 and 0.67, indicating a low diversity. The omnivorous species were found more frequently; especially at the P03 sampling station (95%). Five stations (P01, P02, P04, P05 and P06) had poor water quality and the station (P03) presented a very poor IBI; which allows to accept the idea raised.